Proceedings of the 17th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2014
DOI: 10.1145/2531602.2531619
|View full text |Cite
|
Sign up to set email alerts
|

Supporting group interactions in museum visiting

Abstract: Ethnographic study in two contrasting museums highlights a widespread but rarely documented challenge for CSCW design. Visitors' engagement with exhibits often ends prematurely due to the need to keep up with or attend to fellow group members. We unpack the mechanics of these kinds of phenomena revealing how the behaviours of summoning, pressurizing, herding, sidelining, and rounding up, lead to the responses of following, skimming and digging in. We show how the problem is especially challenging where young c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 34 publications
2
29
1
Order By: Relevance
“…How best to design for integrated family experiences is an open question, and might be informed by studies of how families behave in museums [e.g. see Tolmie et al 2013], and of how family members orientate themselves to the usage of technology in this environment. This paper engages with the latter by presenting a study of a technology deployment in Cité de l'Espace (CITE), a science education center in Toulouse, France.…”
Section: Introductionmentioning
confidence: 99%
“…How best to design for integrated family experiences is an open question, and might be informed by studies of how families behave in museums [e.g. see Tolmie et al 2013], and of how family members orientate themselves to the usage of technology in this environment. This paper engages with the latter by presenting a study of a technology deployment in Cité de l'Espace (CITE), a science education center in Toulouse, France.…”
Section: Introductionmentioning
confidence: 99%
“…Socialization -it is commonplace to visit a gallery or museum as part of a group of family or friends which raises further challenges, from the problems of sharing audio guides [1] to the difficulties that arise from splitting attention between artifacts and information on the one hand and the needs of fellow visitors on the other, which in some circumstances can lead to a near constant state of interruption as visitors prematurely disengage from the former in order to keep up with the latter [31]. Studies of visitor behavior have shown that collaborative interaction shapes how visitors experience museums and their objects [11,33] and it is becoming more common for visiting technologies to incorporate social functions such as allowing visitors to share expressive responses [15] and make connections with others around objects [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these implications stand in contrast to previous research on interaction in museums and galleries that has emphasised the importance of supporting group visiting [34], highlighted the challenges of wearing headphones [1] and focused on the importance of collaborative displays [16]. Our experience suggests an alternative strategy, one of isolation leading to deep engagement.…”
Section: Congruencementioning
confidence: 59%